USING WEB 2.0 TOOL PODCAST IN TEACHING FOREIGN LANGUAGES - Radoslav Stefancik; Eva Stradiotová (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2020)
Web 2.0 has become slowly but surely a part of the teaching and learning process. It is a social network that includes tools such as Facebook, Twitter, blogs, podcasts, wiki, etc. We see the podcast as one of the ways how to motivate students to learn and improve their language skills. The paper analyses the use of the Web 2.0 tool podcast in teaching English and German languages and the impact of using podcasts on the considerable improvement of respondents' listening skills. In academic research, we intentionally used the quantitative method like controlled experiments and questionnaires. 218 respondents who studied the English language and 196 respondents who studied the German language attended the experiment. Respondents were randomly divided into experiment and control groups. The experiment was carried out during 13 weeks of the winter term. After analysing the input and output data achieved from the pre-tests, post-tests, and questionnaire, we reached the conclusion that podcasts that are used as the support of traditional educational processes in the classroom can help students to significantly improve listening skills.